Change in the surface roughness and surface free energy of Samama (Anthocephalus macrophyllus) after citric acid impregnation through pre-compression method. Issue 6 (19th March 2022) - Cahyono, Tekat Dwi; Dwianto, Wahyu; Darmawan, Wayan; Sakagami, Hiroki
Abstract: This research aims at detecting the hydrophobicity change in Samama ( Anthocephalus macrophyllus ) wood surface after hydro-thermo-mechanical modification. The modification started by soaking the test piece until water-saturated, followed with pre-compression at 100 °C for an hour. The second stage was impregnation of citric acid 10% using autoclave at pressure 7.5 kg cm −2 for 4 h. The other test piece was only impregnated using distilled water, without citric acid, with the same pressure within the same time. Further, the second compression was conducted on the test piece impregnated only with distilled water and citric acid. It was conducted at 180 °C for 10, 20, 30, 40, 50 and 60 min. The compaction target was 20%. After conditioning for 2 weeks at room temperature (25 °C) and RH 85%, the test piece was soaked in distilled water for 24 h for the spring back test. The surface roughness and surface free energy were tested after the spring back test. The test result shows that the tangential surface of Samama wood impregnated with citric acid and compressed for 50 min (type CA50) has the smoothest tangential surface. The type also has the lowest SFE value of 36.193 mJ m −2 . In addition, the dispersive component of densified Samama wood surface seems to increase and, on the contrary, its polar component is reduced. The wood radial surface impregnated with citric acid tends to be rougher with a higher total SFE value than that of the tangential surface.